Antecedents and Consequences of Brand Love: The Moderating Effect of Brand Love (Lex localis - Journal of Local Self-Government, 2025)
This study investigates how brand satisfaction, brand trust, brand love, brand loyalty, and word of mouth are interlinked through the Starbucks brand. Specifically, It examines the moderating role of brand love on the brand satisfaction-brand loyalty and brand trust-brand loyalty relationships. A survey is conducted with 475 undergraduate students who visit Starbucks stores; although, A pre-test is conducted to revise the questionnaire. We conduct descriptive statistics, reliability analysis, validity analysis, and path analysis using the AMOS software. The study’s results reveal that brand satisfaction and brand trust have a positive and statistically significant relationship with brand love and brand loyalty. Further, the results indicate that brand love has a positive effect on brand loyalty, which, in turn, leads to positive word of mouth. However, brand love only moderates the relationship between brand satisfaction and loyalty. Finally, our results provide practical implications and directions for future research.